Romantic Fantasy as Reflected in Stephanie Meyer's New Moon - Manoppo, Sri Wahyuni; Oroh, Elisabeth Z.; Muntuuntu, Meity (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study attempts to examine Meyer's New Moon romantic fantasy. John G. Cawelti's theory is the one that gets applied. In this study, the researcher used objective research as a research design. The source of data collection consists of primary data, namely novel and the New Moon novel itself and secondary data which includes articles and books from the internet that support this research. The researcher conducted this research using a close reading approach, which is to analyze in detail and in depth to find the meaning. The data used in this research is the novel New Moon. Based on the results of the research, from this study is that Meyer’s New Moon reflected the romantic fantasy which the strong competent female character namely Bella who have love affair with a vampire as Edward in a supranatural world. This couple faced to challenges because they from a different world.